Perancangan Sistem Pemesanan Makanan Berbasis Website Pada sushiBROK - Haren Sandhya Wichaksana Hariono (Indonesian Journal of Education And Computer Science, 2024)
The Design of Food Ordering System Based on Website at sushiBROK is an effort to introduce innovation in the restaurant industry by leveraging digital technology. This research aims to develop an online platform that allows customers to order food easily and efficiently through the website. By applying needs analysis, system design, implementation, and testing, this system is designed to enhance customer experience and improve restaurant operational efficiency. Through this system, customers can explore the menu, order food according to their preferences, and make online payments. Additionally, order tracking features will also be provided to monitor the status of orders in real-time. It is hoped that this ordering system will assist sushiBROK in optimizing customer service, reducing waiting time, and enhancing customer satisfaction. The implications of this research are not only limited to improving restaurant operational performance but also create opportunities to expand market share and enhance competitiveness in the increasingly competitive culinary industry. The results of this research enable buyers to easily order food through the website, potentially increasing the number of buyers due to its easy and fast ordering process